The tendency of Islamophobia and Comportment of the World: Analytical Study (Al-Qamar, 2021)
Islamophobia denotes discriminatory tendency and racism against Islam perceivers. A pol-religion originated concept is not just a phenomenon but is growingly deployed for a new zone of the research study in social sciences. It also raised controversy on its reference to religion.  Western philosophy of equal rights and a safe area for minorities is under question. The article describes the frequent incidents of Islamophobia. It highlights the causes and impacts of Islamophobia on global society.  This research paper will also explore the role of Pakistan in this crucial tendency. This paper will assist in further research and study this field deeply. It will present the points countering such discriminatory behavior.
Keywords: Islamophobia; Anti-Muslim; Discrimination; Islam; West